The relationship between out‐of‐pocket healthcare expenditures and insurance status among individuals with chronic obstructive pulmonary disease. Issue 2 (26th February 2017) - Kang, Hyeun Ah; Barner, Jamie C.
Abstract: Objectives: To assess the relationship between out‐of‐pocket (OOP) healthcare expenditures and insurance status among subjects with chronic obstructive pulmonary disease (COPD). Methods: A retrospective database study using the 2012 Medical Expenditure Panel Survey was conducted. Adults (≥18 years) with a COPD diagnosis who received COPD‐related healthcare services at least once in 2012 were included. The dependent variable was annual OOP expenditures and the independent variable was health insurance type. Descriptive statistics, regression for complex sampling design and a two‐part model (TPM) were conducted using SAS and STATA. Key findings: Subjects' ( N = 587 unweighted; N = 5, 982, 925 weighted) total mean ± SE OOP COPD expenditures were $236.2 ± 45.1. TPM analysis showed that there was no difference in having OOP expenditures versus no OOP expenditures by insurance status. Among those having OOP expenditures, compared to subjects with private insurance, those with no insurance had 4.8 times higher OOP expenditures (OR; 95% CI: 4.754 (2.069, 10.935)). Inpatient OOP expenditures and ambulatory care visit OOP expenditures were significantly higher for subjects with no insurance ($4, 631.7 ± 1, 753.7 and $77.9 ± 14.0 respectively) than for those privately insured ($186.9 ± 167.8 and $35.0 ± 5.3 respectively). Regarding prescription expenditures, there were no statistically significant differences in OOP expenditures when stratified by insurance status. Conclusions: Compared to insured subjects, those with no insurance had higher OOP expenditures for COPD‐related total, inpatient and ambulatory care services. No statistical difference was noted in OOP expenditures for prescriptions. The Affordable Care Act may be beneficial in reducing OOP expenditures for those who were not insured.